1795 Mass. Gen. Laws ch. 2, § 2; 1795 Mass. Acts 436 - (:unkn) unknown (My University, 1795)
Commanded justices of the peace to arrest "all affrayers, ruiters, disturbers, or breakers of the peace, and such as shall ride or go armed offensively, to the fear or terror of the good citiens of this Commonwealth."
Keywords: GOING ARMED; SURETY